Management of Educational Financing Plan at Madrasah Aliyah Darul 'Amal Karanganyar - Yanto; Supriyanto (Presscience, 2023)
Educational financing planning management is a set of work implementation management processes that includes planning in educational organizations related to the determination of money received as the amount of income originating from individuals or groups of institutions within a certain period of time as a form of compensation that has been donated to educational institutions. The purpose of this study is to describe the strategy in managing education financing planning at Madrasah Aliyah Darul 'Amal Karanganyar. This research is a type of qualitative research with data collection techniques by observation, interviews and documentation. Data analysis through data reduction, data presentation, and drawing conclusions. Test the validity of the data with data triangulation. The selection of subjects and informants was based on the order of the head of the madrasa, deputy head of the madrasa for curriculum and treasurer of the madrasa. The results showed that the management of educational financing planning at Madrasah Aliyah Darul 'Amal Karanganyar was carried out through an inventory of plans to be carried out, preparation of program plans with priority scales, determination of work program details, determination of the need for implementation of program details, calculation of the funds needed, and determination of sources of funds in the framework of financing education at Madrasah Aliyah Darul 'Amal Karanganyar on the academic year 2022/2023.